Diets of peracarid crustaceans associated with the orange coral Astroides calycularis in southern Spain - TERRÓN-SIGLERA, A.; LEÓN-MUEZ, D.; PEÑALVER-DUQUE, P.; ESPINOSA TORRE, F. (Mediterranean Marine Science, 2015)
The endangered and Mediterranean endemic orange coral (Astroides calycularis) hosts an important macrofaunal assemblage. The gut contents of the main peracarids associated with the orange coral were analysed. In total 161 specimens belonging to 11 species and 9 families were examined on the southern coast of the Iberian Peninsula. The gut content study was carried out introducing the specimens of each species in Hertwig’s liquid. The analysis revealed that the peracarid species associated with A. calycularis had different feeding strategies and their main food source was detritus. The results highlight that peracarids may depend on the host and the detritus that the coral produces.